(3GbJUGOjGJ GdfbhO hGdHfhc (B:s (3GdCSGSjGJ (B/s - (3GdQaGYj, ZGdH YhVs; (3HdYQHj, YHO GdMajX s ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2002)
(3GdeONd(B-(3GdfXGe GdeGdj(B-(3GdfbhO(B-(3CSYGQ GdaGFOI(B-(3fXQjI GNJjGQ GdeMaXI GdeGdjI(B-(3JbdHGJ CSYGQ GdaGFOIs
(3cTGa eUWdMGJ U(B.193 (3HHdjhZQGajG(B: (3U(B.192s
Keywords: (3GdHfhcs; (3GdfbhOs